2019
DOI: 10.1590/rbz4820170286
|View full text |Cite
|
Sign up to set email alerts
|

Fiber source and xylanase on performance, egg quality, and gastrointestinal tract of laying hens

Abstract: The objective of this study was to ascertain the influence of different dietary fiber sources and the usage of xylanase on diet of commercial layers and their influence on productive performance, egg quality, and digestive organ biometry. A total of 864 Lohmann ® White hens was fed diets with three different fiber sources (wheat bran, soybean hull, or coffee husk) with or without xylanase inclusion (concentration of 160,000 BXU/g) in a 3×2 factorial arrangement, with six replicates of 24 birds each, from 25 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 15 publications
5
21
0
1
Order By: Relevance
“…The quality of produced eggs was negatively affected by feeding laying hens with by-products of caffeine-containing plants, such as coffee husks ( 3 ), cocoa bean shell ( 4 ), and green tea powder ( 6 , 7 ). In this study, caffeine ingestion negatively affected the production and quality of eggs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The quality of produced eggs was negatively affected by feeding laying hens with by-products of caffeine-containing plants, such as coffee husks ( 3 ), cocoa bean shell ( 4 ), and green tea powder ( 6 , 7 ). In this study, caffeine ingestion negatively affected the production and quality of eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental design was completely randomized of four treatments with three different amounts of caffeine (anhydrous caffeine, Sulfal, Belo Horizonte, MG, Brazil) per ton of feed: 0 (control), 150, 300, and 450 g/ton. The highest concentration was based in an earlier study that showed impaired egg production by laying hens fed coffee husks at 42.5 g/kg ( 3 ), that is expected to contain caffeine at ~10.0 mg/g ( 12 ), equal to 425 g of caffeine/ton of feed. Ingredients and nutritional composition of the basal diet are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations